1990
DOI: 10.1590/s0037-86821990000100012
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição ao estudo da anatomia patológica e da patogênese do megaesôfago chagásico

Abstract: F oram analisadas e com paradas as alterações morfológicas das diversas camadas de 56 esôfagos de chagásicos crônicos (17 com e 39 sem mega) e de 26 não chagásicos. Com base nos achados morfométricos obtidos e em dados obtidos e em dados da literatura, considerou-se como megaesôfago (M E) os casos, cujo diâmetro do órgão ultrapassou 2,5 cm, na ausência de qualquer obstáculo mecânico.M acroscopicam ente, a parede do órgão apre sentou-se espessada em treze casos (76,5% ), normal em três (17,7% ) e diminuída em u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This could explain the higher frequency of idiopathic megaesophagus (achalasia) compared with idiopathic megacolon. It would also allow more severe denervation of the esophagus compared with the colon, favoring earlier onset of megaesophagus compared with megacolon 6 , 19 , 20 , 21 , despite the need for a higher degree of denervation in megaesophagus than in chagasic megacolon 1 , 2 , 3 , 4 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain the higher frequency of idiopathic megaesophagus (achalasia) compared with idiopathic megacolon. It would also allow more severe denervation of the esophagus compared with the colon, favoring earlier onset of megaesophagus compared with megacolon 6 , 19 , 20 , 21 , despite the need for a higher degree of denervation in megaesophagus than in chagasic megacolon 1 , 2 , 3 , 4 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…According to GABELLA (1990), “a single basal lamina surrounds the entire ganglion and no collagen fibrils, connective cells or blood vessels are found inside ganglia”. However, ADAD described the presence of blood vessels in ganglia of the myenteric plexus of the human esophagus 1 , although such vessels were not identified in colonic ganglia 2 . Nevertheless, these studies were performed on histological sections stained by hematoxylin-eosin (H&E) and Giemsa only, and they were not conducted in a systematized manner to investigate the vascularity of the ganglia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by Cunha-Neto et al (1998 ) have demonstrated a role for CD4+ T cells in reacting with self cardiac myosin. Adad et al (1991) demonstrated that patients with the gastrointestinal clinical form of the disease present lesions of the myenteric plexus. Tafuri et al (1971) demonstrated that microscopically, the inflammatory infiltrates composed primarily of small lymphocytes that are found mainly in the muscularis propria and in the myenteric nervous system and are often associated with a striking reduction in the number of enteric neurons.…”
mentioning
confidence: 99%